1987
DOI: 10.1891/0886-6708.2.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Crime at Home and in the Streets: The Relationship between Family and Stranger Violence

Abstract: Research and theory on violent behavior have treated aggression between intimates and aggression between strangers as separate phenomena. Major criminological works on violence and aggression have generally overlooked violence in the home. As a result, independent and distinct bodies of theoretical and practical knowledge exist regarding family violence and aggression toward strangers, and the relationship between family violence and violence directed against strangers is little understood. Estimates of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 0 publications
3
49
0
1
Order By: Relevance
“…Empirical support for these variables is found in the literature on Census data methodology, 12,13 in published studies that analyzed neighborhood-level characteristics in relation to interpersonal violence, 10,[16][17] and in a theoretical model of family violence that locates the sources of domestic violence at the individual, situational, environmental, and ideological levels of explanation. 29 We theorized that: (a) Concentration of poverty provides information on the neighborhood tax base for important services and resources, on housing stock, and on public safety. (b) Concentration of college graduates provides information on skills, prestige, and opportunities to access resources.…”
Section: Study Samplementioning
confidence: 99%
“…Empirical support for these variables is found in the literature on Census data methodology, 12,13 in published studies that analyzed neighborhood-level characteristics in relation to interpersonal violence, 10,[16][17] and in a theoretical model of family violence that locates the sources of domestic violence at the individual, situational, environmental, and ideological levels of explanation. 29 We theorized that: (a) Concentration of poverty provides information on the neighborhood tax base for important services and resources, on housing stock, and on public safety. (b) Concentration of college graduates provides information on skills, prestige, and opportunities to access resources.…”
Section: Study Samplementioning
confidence: 99%
“…Trends in domestic violence rates over the past 10 years have documented a decrease and it appears new social norms regarding domestic violence may have emerged (see Klein et al, 1997), which suggest a relation between domestic violence policies and underlying social norms. Alternatively, there has been much research examining the effectiveness of arrest policies (Berk & Newton, 1985;Buzawa & Austin, 1993;Feder, Jolin, & Feyerherm, 2000;Maxwell, Garner, & Fagan, 2001;Schmidt & Sherman, 1993;Sherman & Berk, 1984;Tolman & Weisz, 1995) and some research examining the effects of varying prosecutorial policies (Davis, Smith, & Nickels, 1998;Fagan, Friedman, Wexler, & Lewis, 1984;Feder et al, 2000;Ford & Regoli, 1993); however, this research has revealed mixed results (Maxwell, Garner, & Fagan, 2001). For example, some studies have shown arrest to be an effective deterrent against future offending (Berk & Newton, 1985;Sherman & Berk, 1984), whereas other studies indicate arrest is effective only for a certain profile based on offender characteristics (e.g., employed, White, and Hispanic; Schmidt & Sherman, 1993).…”
Section: Theoretical Perspectives On Policies and Social Normsmentioning
confidence: 99%
“…Still other studies have shown that arrest may backfire, where violence increases following arrest, or that arrest has no effect on future violence (Schmidt & Sherman, 1993). Some evaluations of prosecutorial practices indicate that prosecution versus no prosecution has no deterrent effect on future violence (Davis, Smith, & Nickels, 1998;Fagan et al, 1984). Yet, Ford and Regoli (1992) found in their evaluation of prosecutorial policy that prosecution resulted in less future violence.…”
Section: Theoretical Perspectives On Policies and Social Normsmentioning
confidence: 99%
“…Alguns consideram que o problema acontece devido a uma carência emocional experimentada pela criança que se sente ferida; outros acreditam que a criança não teve fixados os seus limites. Perceberam que crianças e adolescentes desvantajados, expostos ao abandono, morte ou doença dos pais, ou submetidos à intensa ansiedade gerada pelo ambiente das ruas, podem apresentar conduta agressiva (Fagan & Wexler, 1987). Quando os pais ferem-se mutuamente, abandonam as famílias ou ameaçam suicidar-se, a ansiedade dos filhos é esmagadora.…”
Section: O Adolescente Agressivo E Maltratadounclassified